Nonparametric analysis of household labor supply: goodness-of-fit and power of the unitary and the collective model - Laurens Cherchye; Frederic Vermeulen (Institute for the Study of Labor (IZA), 2006)
We compare the empirical performance of unitary and collective labor supply models, using representative data from the Dutch DNB Household Survey. We conduct a nonparametric analysis that avoids the distortive impact of an erroneously specified functional form for the preferences and/or the intrahousehold bargaining process. Our analysis focuses on the goodness-of-fit of the two behavioral models. To guarantee a fair comparison, we complement this goodness-of-fit analysis with a power analysis. Our results strongly favor the collective approach to modeling the behavior of multi-person households.
Keywords: C14; D12; J22; 330; labor supply; collective model; unitary model; nonparametric analysis; revealed preferences; Arbeitsangebot; Privater Haushalt; Nichtparametrisches Verfahren; Offenbarte Präferenzen; Theorie; Niederlande